2009
DOI: 10.1038/jcbfm.2009.187
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of Stroke with a Synthetic Liver X Receptor Agonist, TO901317, Promotes Synaptic Plasticity and Axonal Regeneration in Mice

Abstract: In this study, we tested the hypothesis that TO901317 promotes synapse plasticity and axonal regeneration after stroke. Adult male C57BL/6J mice were subjected to middle cerebral artery occlusion (MCAo) and treated with or without TO901317 starting 24 h after MCAo daily for 14 days. Axonal damage and regeneration were evaluated by immunostaining. TO901317 significantly increased synaptophysin expression and axonal regeneration, as well as decreased the expressions of amyloid betaA4 precursor protein and Nogo r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
54
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(56 citation statements)
references
References 45 publications
2
54
0
Order By: Relevance
“…LXR activation promotes synaptic plasticity and axonal regeneration in stroke patients (11) and is required for dopaminergic neuron differentiation, which is useful for Parkinson's disease treatment (4,20). In Alzheimer's disease, LXR activation increases the number of cholinergic neurons and attenuates cognitive impairment by blocking the inflammatory process (12).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…LXR activation promotes synaptic plasticity and axonal regeneration in stroke patients (11) and is required for dopaminergic neuron differentiation, which is useful for Parkinson's disease treatment (4,20). In Alzheimer's disease, LXR activation increases the number of cholinergic neurons and attenuates cognitive impairment by blocking the inflammatory process (12).…”
Section: Discussionmentioning
confidence: 99%
“…Given that the modulation of the LXR pathway is already beneficial for the treatment of other pathologies of the nervous system (11,12), our observations open new perspectives for the development of therapies targeting LXRs in demyelinating diseases.…”
Section: Lxr Activation Increases Remyelination In Cerebellar Organotmentioning
confidence: 99%
“…The results presented here on increased hippocampal AChE and synaptophysin protein levels in the pre-lesion TO901317-treated mice are certainly consistent with these observations. They are also supported by the work of Chen et al (2010) showing that TO901317 administration stimulates synaptic remodeling and axonal regeneration in an experimental model of stroke in the mouse.…”
Section: Discussionmentioning
confidence: 69%
“…Following acclimatization, a subgroup of mice were randomly assigned to receive daily intra-peritoneal injections of 30 mg/kg/day of TO901317 in 0.125% (wt/vol) carboxymethycellulose (CMC) at one of two different starting time points and continued until sacrifice in order to assess the therapeutic potential of the treatment as prevention (7 days before lesion (ECL); n = 5) or rescue (7 days after lesion (ECL); n = 5). The choice of the 30 mg/kg/day dose was guided by previous studies which reported beneficial outcomes of TO901317 in the CNS (Chen et al, 2010;Morales et al, 2008;Riddell et al, 2007). Furthermore, a prior pilot study was conducted in our laboratory using a small set of animals.…”
Section: Lxr Agonist Administrationmentioning
confidence: 99%
“…Another possibility is that PI3K gene transcription is coordinately regulated by LXR, because the results showed that TO901317 treatment also increased PI3K enzyme activity. Similarly, previous research has shown that in vitro primary cortical neuron culture TO901317 treatment significantly increased the p-PI3K and p-AKT activity (Chen et al, 2009). Otherwise, we observed when TO901317 concentration reached 10 μmol/L, the expression of PI3K/AKT/mTOR remained a significant high level, but the SREBP-2 mRNA level and the intracellular cholesterol concentration decreased.…”
Section: General Remarksmentioning
confidence: 99%